2022
DOI: 10.1177/01614681221093286
|View full text |Cite
|
Sign up to set email alerts
|

“Immigration Knocks on the Door . . . We Are Stuck . . .”: A Multilevel Analysis of Undocumented Youth’s Experiences of Racism, System Failure, and Resistance in Policy and School Contexts

Abstract: Background/Context: Undocumented youth navigate unwelcoming federal, state, and local contexts in the United States. Although previous research shows the significant impact of immigration policy and enforcement on educational outcomes and social-emotional well-being, this study sheds light on the multiple, intersecting policy, and school contexts that hinder social and educational mobility. Purpose: The purpose of the study is to elicit Latinx undocumented immigrant youth experiences in a southern state to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The study was guided by an overarching research question: How do undocumented high school youth in a southern state talk about their perceptions of citizenship in relation to their undocumented status and racial and ethnic identities? The research contributes to previous theoretical discussions of citizenship and brings together previous studies of how citizenship status is racialized (Menjívar 2021;Rodriguez 2022), specifically theorizing racialized citizenship, from youth perspectives, through racial scripts (Molina 2014) and underscoring youth's relational and resistive dimensions of citizenship as well as their responses to institutional forms of citizenship (Molina 2014). We argue that the notion of racialized citizenship through racial scripts is critical for understanding how Latinx immigrant youth are socially positioned within U.S. racial hierarchies.…”
Section: Purpose and Contributionmentioning
confidence: 68%
See 1 more Smart Citation
“…The study was guided by an overarching research question: How do undocumented high school youth in a southern state talk about their perceptions of citizenship in relation to their undocumented status and racial and ethnic identities? The research contributes to previous theoretical discussions of citizenship and brings together previous studies of how citizenship status is racialized (Menjívar 2021;Rodriguez 2022), specifically theorizing racialized citizenship, from youth perspectives, through racial scripts (Molina 2014) and underscoring youth's relational and resistive dimensions of citizenship as well as their responses to institutional forms of citizenship (Molina 2014). We argue that the notion of racialized citizenship through racial scripts is critical for understanding how Latinx immigrant youth are socially positioned within U.S. racial hierarchies.…”
Section: Purpose and Contributionmentioning
confidence: 68%
“…Critical to this access, she shared experiences as a teacher, researcher, and first-generation, Latinx Cuban female to build relationships and trust with youth. Sophia discusses elsewhere how the "stories we held in common" as children of immigrants, specifically that her father was a Cuban refugee, shape her research and activism with Latinx immigrant communities and promoted a sense of connection with youth despite being a U.S. citizen (Bettie 2003;Rodriguez 2020Rodriguez , 2022. The two sites were selected for their rising population of Latinx undocumented students.…”
Section: Site Selection: Citizen North and Denizen Westmentioning
confidence: 99%
“…Student activism (Gonzales, 2008;Negrón-Gonzales, 2015;Escudero, 2020;Terriquez et al, 2018) and resistance movements (Buenavista, 2018;Pérez Huber, 2017;Rodriguez, 2022) were instrumental in demanding equitable opportunities and resources for undocumented students, drawing significant attention and leading to policies like DACA that temporarily widened access to employment and higher education. A recent report by the President's Alliance on Higher Education and Immigration (2021) found that there were approximately 427,000 undocumented students, with about 181,000 of them who were DACA-eligible.…”
Section: Undocumented Students In Higher Education Daca and Its Limit...mentioning
confidence: 99%
“…This book offers an examination of the history of immigration enforcement policies, the effects of the pandemic, the role of teachers, ICE and police partnerships in local communities, and a model of sanctuary schooling. Building upon recent scholarship that separately analyzes school‐based personnel (Rodriguez & Crawford, 2021; Rodriguez, et al, 2021; Rodriguez, 2022), Gándara and Ee disrupt the notion that immigration policies can be separate from education policies. Given the invasive immigration enforcement apparatus into multiple sectors of immigrants’ everyday lives (Menjívar, 2014; Verma et al, 2017), this book exposes the uncomfortable truth that immigration authorities and lawmakers must be aware of the impact their actions have on children.…”
mentioning
confidence: 99%